Criminal liability for the commission of war crimes: analysis of the corpus delicti of unlawful encroachments - V. V. Sokurenko (Bulletin of Kharkiv National University of Internal Affairs)
The need for a criminal law analysis of military-violent crime is substantiated given the ongoing armed conflict in Ukraine, the annexation of some of its territories and the open calls of the russian authorities to destroy the Ukrainian nation and incite hatred towards everything that identifies Ukraine as a sovereign independent state. The classification of war crimes in the context of the armed conflict in Ukraine is proposed depending on the category of victims Military violent crimes in the context of the armed conflict in Ukraine should be divided into two groups of offences depending on the category of victims. The first group of such unlawful encroachments includes war crimes against the civilian population (Article 433; parts 1 and 2 of Article 438 of the CCU – violation of the laws and customs of war regarding rape and sexual violence, enslavement and torture, forced displacement of civilians, intentional killing of civilians; Article 442 of the CCU). The second group of military-violent offences includes military-violent crimes against servicemen (Article 434 of the Criminal Code of Ukraine; Part 1 of Article 438 of the Criminal Code of Ukraine – violation of the laws and customs of war regarding the ill-treatment of POWs, including cases of use of prohibited means and methods of warfare, as a result of which a serviceman was recognised as a victim).